Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
:Table of Content• Social Responsibility at King Saud University and Its Relationship with Academic Satisfaction from the Perspective of Graduate StudentsMr. Ibrahim Nasser Saud Al-Maatash• The Educational Implications of Hadiths on the Chapter on Honoring Parents and Maintaining Kinship Relations from Riyad Al- Salihin book and Their Contemporary ApplicationsMr. Rafid Shalwan As- Salami• The Effectiveness of a Supervision Program in Developing the Counselling Supervision Skills of Student Guidance Female Supervisors at the Directorate General of Education in Makkah ProvinceDr. Amjad Ibrahim Al-Sharif, Dr. Hanan Abdulrahim Al-Malki• Redefining Educational Leadership in the Sultanate of Oman: From Standardization to Empowerment within a Paradigm ShiftMr. Saif Hamad Khamis Aljaradi, Prof. Rahmatoallh Marzooghi, Prof. Jafar Torkzadeh, Dr. Elham Heydari• The degree of use of the Artificial Intelligence Application (ChatGPT) by Arab Open University students in psychological counsellingDr. Moosa Sulaiman Al-Shuaili, Ms. Elham AbdulRahman Al-Riyami• Standardization of a scale for social competence of children aged 4–6 years; A field study in kindergartens in the interior regions of IsraelMs. Ehlas Ibrahem Nahle• The Formal Flaws of the Achievement Test Paper and Their Impact on Visual Processing Among General Education StudentsMr. Ibrahim Abdullah Altoum
Keywords: Journal of Educational and Psychological Sciences